Total laparoscopy-assisted total gastrectomy with Da Vinci robotic system conducted by robotic enhanced neurocomputing joint intelligence gastrointestinal surgery hub (RENJI-GISH): a preliminary clinical study and case report - Zihang Liu; Jiayi Gu; Yeqian Zhang; Long Bai; Yujing Guan; Bo Ni; Haoyu Zhang; Muerzhate Aimaiti; Puhua Zhang; Xiaoyao Shen; Shuchang Wang; Ben Yue; et al. (World Journal of Surgical Oncology)
Abstract Background On August 7, 2024, the inaugural total laparoscopy-assisted total gastrectomy with the Da Vinci robotic system was performed in the department of gastrointestinal surgery of Renji Hospital, Shanghai Jiaotong University School of Medicine. The procedure, conducted by RENJI-GISH, employed the use of a Da Vinci robot system in conjunction with the Vision Pro and SonoScape medical electronic endoscopy system. This phenomenon has not been documented in the field of gastric cancer surgery The objective of this study is to investigate the safety, feasibility, and surgical effect of the first total laparoscopy-assisted total gastrectomy with the Da Vinci robotic system, conducted by the Robotic Enhanced Neurocomputing Joint Intelligence Gastrointestinal Surgery Hub (RENJI-GISH). Case presentation A 71-year-old male patient was admitted to the hospital with a six-month history of nausea and vomiting. A gastric malignant tumor was identified through gastroscopic examination. The patient was diagnosed with cardiac adenocarcinoma by gastroscopy and pathology, and there were clear indications for surgical intervention, though no contraindications were identified. On August 7, 2024, the patient underwent a robot-assisted total laparoscopic gastrectomy under general anesthesia. During the surgical procedure, the Vision Pro and the electronic endoscopy system played a pivotal role in accurately identifying the location of the gastric lesions, confirming the resection margin of the tumor, and ensuring the safety of the anastomosis. The intraoperative blood loss was 20 ml, and the operative time was 180 min. On the third postoperative day, the patient passed flatus and was transitioned to a liquid diet on the fourth postoperative day. The patient was discharged on the seventh postoperative day, having not experienced any complications. The postoperative pathology report indicated that the lymph node dissection was complete (0/32), and no evidence of malignancy was identified in the upper and lower resection margins. Conclusions This case study illustrates the safety and feasibility of total laparoscopy-assisted total gastrectomy with the Da Vinci robotic system, performed by the robotic enhanced neurocomputing joint intelligence gastrointestinal surgery hub (RENJI-GISH). Further investigation and experimentation are necessary to fully elucidate the potential of this approach.